Analisis Hubungan Jumlah Beban Pencemar Terhadap Kualitas Air Permukaan Menggunakan Perangkat Lunak SPSS 23 - Disnanda Utamifa Jannahdita; Okik Hendriyanto Cahyonugroho (Yayasan Literasi Sains Indonesia, 2023)
The amount of surface water pollutant load in the upstream tends to be lower when compared to the amount of surface water pollutant load in the downstream, this is due to the flow of water flowing from upstream to downstream and resulting in changes in surface water quality. Therefore, the purpose of this study is to understand the relationship between the level of surface water pollutant load in the upstream and downstream areas of Greges River, Surabaya by utilizing SPSS 23 software. The analysis method utilized refers to the simple linear regression method. The results of the analysis showed that with a significance level of less than (<) 5%, it can be concluded that there is an indication of an acceptable relationship between upstream surface water quality and downstream surface water quality. Simultaneously, the upstream surface water quality has a significant effect on the downstream surface water quality of Greges River, with the level of relationship reaching 85.7%, meaning that there is a very strong linear relationship between the upstream surface water quality and the downstream surface water quality it produces.